Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities. Issue 2 (17th January 2017) - Mei, Shuang-Xi; Li, Xu-Hong; Yang, Li-Guo; Li, Xiao-Hui; Xie, Jia-Ying; Yao, Qi; Su, Mei; Cui, Tao; Wang, Jing-Kun; Zhu, Zhao-Yun
Abstract: Two new aromatic glycosides, 2-methylphenyl O - β -d -xylopyranosyl-(1→6)- O - β -d -glucopyranoside (1 ) and 2-methylphenyl O - α -arabinofuranosyl-(1→6)- O - β -glucopyranoside (2 ), together with eight known compounds were isolated from the roots of Ampelopsis delavayana. Their structures were elucidated on the basis of extensive spectroscopic analysis. Furthermore, the in vitro antibacterial activities of1 and2 were investigated using serial twofold dilution in three bacteria including Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus . Abstract :